Pengembangan e-learning untuk persiapan uji kompetensi ners indonesia (UKNI) - Nugroho, Tri Adi; Haryanti, Fitri; Lazuardi, Lutfan (Wellness And Healthy Magazine, 2019)
Background: The era of globalization bring nursing education institutions in Indonesia run nursing education process varies with the quality control system education that goes well, but not optimal so that the quality of graduates is very diverse. One of the efforts to realize the improvement of the quality and equity of health workers is to improve the quality control of graduates through the competency test. Meanwhile, the utilization of information and communication technology (ICT) -based e-learning is a new paradigm in health education. The need for nurses prepares for a competency test into an opportunity for universities to take advantage of ICT-based e-learning for nurse competency test preparation. Methods: This study is action research. Stages of research begin with needs analysis through interviews, observation and focus group discussion involving three lecturers and 14 participants UKNI. The results of the needs analysis are used as a reference in designing the prototype e-learning. E-learning prototype evaluation was performed using the theory of the Technology Acceptance Model (TAM). Results: The prototype eLearning developed in accordance with the needs analysis include: the accessibility of e-learning, quality of information, human resources and management content.   The results of the evaluation of the prototype e-learning on perceived usefulness, 51.8% of respondents strongly agree and 47% agree, while the perceived ease of use, 42.9% of respondents strongly agree and 56% of respondents agreed. Conclusions: The need for the development of e-learning for UKNI preparation is the substitution, meaning that learning is done through the internet entirely. The evaluation results usefulness respondents perceived the prototype e-learning was helpful. The results of the evaluation of perceived ease of use of respondents feel the ease operate prototype e-learning.